Zakrasela pokrajina v Frankovski Juri - Pavšek, Miha (Geografski obzornik, 1994)
The first part of an article in previous issue dealt with some basic characteristics of german karst surface and those one of the Franconian Jura which we have known in our common field work with the students from the University of Tübingen (Germany). Improved and detailed knowledge about some surface karst forms enabled us to recognize the oldness of karstification process and, as synthesis, the explanation of karst surface and the basic relief-forms development, which are typical for surveyed area.
Keywords: geografija; jura; kras (geologija); kraški pojavi; Nemčija